2006
DOI: 10.1111/j.1475-6773.2006.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Operational Failures and Interruptions in Hospital Nursing

Abstract: Objective. To describe the work environment of hospital nurses with particular focus on the performance of work systems supplying information, materials, and equipment for patient care. Data Sources. Primary observation, semistructured interviews, and surveys of hospital nurses. Study Design. We sampled a cross-sectional group of six U.S. hospitals to examine the frequency of work system failures and their impact on nurse productivity. Data Collection. We collected minute-by-minute data on the activities of 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
304
1
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(324 citation statements)
references
References 55 publications
11
304
1
8
Order By: Relevance
“…These have been referred to as glitches (Uhlig et al 2002), operational failures (Tucker 2004, Tucker andSpear 2006), performance obstacles (Gurses and Carayon 2007), hassles (Beaudoin and Edgar 2003), blockages (Rathert et al 2012), and situational constraints O'Connor 1980, Villanova andRoman 1993). In this paper, we refer to them as operational failures.…”
Section: Prior Research On Operational Failures and Lean Manufacturinmentioning
confidence: 99%
“…These have been referred to as glitches (Uhlig et al 2002), operational failures (Tucker 2004, Tucker andSpear 2006), performance obstacles (Gurses and Carayon 2007), hassles (Beaudoin and Edgar 2003), blockages (Rathert et al 2012), and situational constraints O'Connor 1980, Villanova andRoman 1993). In this paper, we refer to them as operational failures.…”
Section: Prior Research On Operational Failures and Lean Manufacturinmentioning
confidence: 99%
“…31 Furthermore, researchers have demonstrated that systems issues can add substantially to nursing workload. 32 Methods such as those described in our study take into account both patient-related and systems-related tasks, and therefore could result in more detailed workload assessments. With more detailed information about contributors to workload, better predictions about optimal staffing could be made, which would ultimately lead to fewer adverse patient events.…”
Section: Discussionmentioning
confidence: 99%
“…These systems problems and the work-arounds nurses used to resolve them equate to a workload of one-third of a patient per nurse and serve to interrupt patient care and create potential safety issues. 3 Results from Dr Tucker's research suggest that efforts to improve systems and processes affecting nursing work need to be thoughtfully managed. Using the measure of perceived improvement, she reported that generating more improvement ideas and identifying the very best idea did not lead to improved performance.…”
Section: The Science Of Health Care Deliverymentioning
confidence: 99%